Faktor Kunci Keberhasilan Perguruan Tinggi Dalam Pengembangan Masyarakat Desa - Anas, M Yusuf Azwar; Adita (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
The study's goal is to identify critical success elements in university-led village development programs. A quantitative technique was used, using a sample of 215 respondents. Respondents include residents and stakeholders involved in program execution. The data was gathered via a questionnaire. Factor analysis is used with the SPSS application to process data. That stakeholder commitment and communication with stakeholders are critical factors in determining the success of the village development initiative, for all stakeholders, campuses, and communities. Other aspects include local capacity and social capital. The study's contribution to the strategy of creating tourist villages, particularly the parties involved, including the government, NGOs, and universities, must pay attention to crucial criteria in order for the program to succeed. The study's new approach, in the form of an egalitarian and populist communication technique, can instill confidence and drive in village inhabitants to participate in village development.